Editorial - Suprayitno, Hitapriya (Journal of Infrastructure & Facility Asset Management, 2025)
Finally, JIFAM arrive in the fourth year publication. The JIFAM Volume 4 Issue 1 consists articles related to hydro–infrastructure, road infrastructure, and urban land use related to infrastructure and facility. The JIFAM Editorial Team express their gratitude to the authors who already submitted their papers for the Third Volume.